Negosiasi Sebagai Alternatif Penyelesaian Sengketa Bisnis Di Indonesia - Amar, Rezie Dava; Apriani, Rani; Iman, Candra Hayatul (Jurnal Ilmiah Wahana Pendidikan, 2024)
One of the alternative dispute resolution methods that has long been known and is widely used in business disputes is negotiation. The problem that the author raises is how the negotiation process works in resolving business disputes and what are the advantages of resolving business disputes through negotiation. The research method used is normative juridical research using a statute approach. This research uses secondary data and the research was carried out by searching for information in the literature. The results and conclusions of this research are that the negotiation process in resolving business disputes involves a series of steps or stages from beginning to end, starting from the preparation stage, the negotiation stage and the final stage. Several forms of negotiation techniques that are generally known in society today include competitive, cooperative, soft, hard and interest-based negotiation techniques. The advantage of resolving business disputes through alternative dispute resolution, especially negotiation, is that the goal to be achieved is a win-win solution that is mutually beneficial to the disputing parties, without anyone feeling disadvantaged. Dispute resolution is simpler, the time is relatively fast, the costs are cheap and the confidentiality of the negotiating parties is also guaranteed because the dispute resolution does not involve a third party but the dispute is only resolved by the disputing parties.